OP15 Patients' readiness for advance care planning conversations: a qualitative study as part of the ACTION study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Zwakman, M; Milota, MM; Van der Heide, A; Jabbarian, LJ; Korfage, IJ; Rietjens, JAC; van Delden, JJM; Kars, MC
Abstract : Background: Patients and healthcare professionals describe patients' readiness for advance care planning (ACP) as an indicator for whether or not to start ACP conversations. Nevertheless, it is unclear how readiness manifests and develops throughout an ACP conversation. This study explores patients' readiness during an ACP conversation. Methods: A qualitative study using content analysis of structured ACP conversations between a trained facilitator, a patient with advanced colorectal or lung cancer and a relative. Conversations were conducted in the Netherlands as part of the international ACTION trial. Analysis was supported by NVivo 11. Results: Transcripts of thirteen ACP conversations were included. All patients expressed both signs of not being ready and being ready within one conversation. Signs of being ready included answering questions on a personal level or demonstrating a realistic understanding of one's disease. Signs of not being ready included limiting one's perspective to the here and now or indicating a preference not to talk about an ACP-related topic. Signs of not being ready were especially seen when future oriented topics such as 'complications' and 'hope' were discussed. Patients could more easily elaborate on less future orientated topics as 'good life' and 'earlier experiences with illness'. Despite signs of not being ready patients were able to continue the conversation. Conclusion: Patients do not have to be ready for all elements of ACP to be able to participate in an ACP conversation. Healthcare professionals should be aware of patients' ability to alternate in readiness depending on the topic that is discussed.